Merdeka Curriculum in Developing Soft-Skill Capabilities of Childhood Children at Homeschooling Kak Seto Surabaya - Yulianingsih, Wiwin; Joni Artha , I Ketut Atmadja; Soedjarwo; Mita Lutviatiani; Ahmad Abdullah Zawawi (Jurnal Pedagogi dan Pembelajaran, 2023)
The change in the education curriculum from the 2013 Curriculum (K-13) to the Independent Curriculum is a form of evaluation and an effort to improve the quality of education in Indonesia. This research aims to analyze the implementation of the independent learning curriculum in developing the soft skills of childhood-aged children in homeschooling at PKBM Kak Seto Surabaya. This type of research is qualitative research. The method applied is a qualitative method with a field research approach. The data collection techniques used were participatory observation and semi-structured interviews with administrators and parents of students. The data analysis technique uses qualitative descriptive analysis. The data analysis model applied is the Miles and Huberman model, namely through the stages of data collection, reduction, presentation, and conclusion. The results obtained in this research show that the implementation of the independent curriculum had a big impact on the development of soft skills for children in childhood, carried out by organizing educational programs such as Friday classes, English clubs, and sports activities that can improve soft language skills, the ability to manage emotions ( emotional skills), as well as social skills.